2019
DOI: 10.1111/1365-2656.12946
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variation makes an ectotherm more sensitive to global warming unless thermal evolution occurs

Abstract: 1. To assess long-term impacts of global warming on species, there is growing interest in latitudinal intraspecific patterns in thermal adaptation. Yet, while both mean temperatures and daily temperature fluctuations (DTFs) are expected to increase under global warming, latitudinal differences in the effects of DTFs have not been documented.2. We tested whether low-latitude populations of an ectotherm deal better with greater DTF than high-latitude populations, especially at a high mean temperature close to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 68 publications
(108 reference statements)
4
43
0
Order By: Relevance
“…The expected higher routine growth rates of French larvae can be explained by stronger time constraints (Dmitriew ): due to their higher number of generations per year, French larvae have less time per larval generation than the semivoltine Swedish larvae. This confirms previous results in the study species based on the same set of four populations (Stoks and De Block , Stoks et al ), as well as other sets of high‐ and low‐latitude populations (Shama et al , Debecker et al , Op de Beeck et al , Debecker and Stoks , Verheyen and Stoks ), indicating that the here documented population differences in growth rate reflect general latitudinal differences. While our design cannot completely exclude maternal effects contributing to the latitudinal pattern, we have previously shown for the study species that while size differences in eggs do exist across latitudes, they have no influence on latitudinal patterns in larval growth rates (Shama et al ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The expected higher routine growth rates of French larvae can be explained by stronger time constraints (Dmitriew ): due to their higher number of generations per year, French larvae have less time per larval generation than the semivoltine Swedish larvae. This confirms previous results in the study species based on the same set of four populations (Stoks and De Block , Stoks et al ), as well as other sets of high‐ and low‐latitude populations (Shama et al , Debecker et al , Op de Beeck et al , Debecker and Stoks , Verheyen and Stoks ), indicating that the here documented population differences in growth rate reflect general latitudinal differences. While our design cannot completely exclude maternal effects contributing to the latitudinal pattern, we have previously shown for the study species that while size differences in eggs do exist across latitudes, they have no influence on latitudinal patterns in larval growth rates (Shama et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Given that the lifespan of the study species is ca 10 days (Cordero et al ), the loss of a few days has strong fitness implications. The study species shows striking latitudinal differences in life history, with higher larval growth rates in the multivoltine (3–4 generations per year), low‐latitude populations compared to the semivoltine (2 years per generation), high‐latitude populations (Stoks and De Block , Shama et al , Stoks et al , Debecker et al , Debecker and Stoks , Van Dievel et al , Verheyen and Stoks ). Moreover, we have recently shown in separate studies that the low‐latitude populations of the species have a longer adult lifespan (reported as Supporting Information in Debecker et al ) and higher levels of antioxidant enzymes in the larval stage (Debecker and Stoks ).…”
Section: Introductionmentioning
confidence: 89%
“…maximum DTF of 10 °C (temperatures fluctuate daily between 19 °C and 29 °C) [1][2][3] . Notably, the current thermal regime during summer in shallow ponds at the low latitude (mean of 24 °C and maximum DTF of 10 °C) corresponds to the future thermal regime predicted at the high latitude in 2100 under global warming scenario RCP 8.5 (IPCC 2013).…”
Section: S3mentioning
confidence: 99%
“…Climate change causes increasing temperature and a network of events triggering the response of plants and animals on Earth 6,7 . Although it seems that creatures on earth gradually developed local thermal adaptation, mean temperatures and daily temperature uctuations are still supposed to impact the healthy condition of each creature 8 . Spinach has cold tolerant but heat sensitive characteristics so that the plant may suffer from heat stress during its entire life with in uencing the growth of spinach plant and signi cantly decrease yield and quality 9 .…”
Section: Introductionmentioning
confidence: 99%